Assessment of omega‐3 carboxylic acids in statin‐treated patients with high levels of triglycerides and low levels of high‐density lipoprotein cholesterol: Rationale and design of the STRENGTH trial. Issue 10 (28th September 2018) - Nicholls, Stephen J.; Lincoff, A. Michael; Bash, Dianna; Ballantyne, Christie M.; Barter, Philip J.; Davidson, Michael H.; Kastelein, John J. P.; Koenig, Wolfgang; McGuire, Darren K.; Mozaffarian, Dariush; Pedersen, Terje R.; Ridker, Paul M.; et al.
Abstract : It is uncertain whether omega‐3 fatty acids are beneficial in statin‐treated patients. Epanova is a mix of omega‐3 free fatty acids, not requiring co‐ingestion with food, which can lower triglycerides by up to 31%. STRENGTH will examine whether Epanova 4 g daily reduces the rate of cardiovascular events in statin‐treated patients with hypertriglyceridemia and low levels of HDL‐C at high risk for developing cardiovascular events. STRENGTH is a randomized, double‐blind, placebo‐controlled trial. Patients had a triglyceride level ≥ 180 to <500 mg/dL and HDL‐C < 42 mg/dL (men) or < 47 mg/dL (women) in the presence of either (1) established atherosclerotic cardiovascular disease, (2) diabetes with one additional risk factor, or (3) were other high‐risk primary prevention patients, based on age and risk factor assessment. Patients should be treated with a statin, for >4 weeks, and have LDL‐C < 100 mg/dL, but were also eligible if LDL‐C was ≥100 mg/dL while on maximum tolerated statin therapy. The study will extend from October 30, 2014 to October 30, 2019. 13 086 patients were randomized to Epanova 4 g or placebo daily in addition to standard medical therapy. The primary efficacy outcome is time to first event of cardiovascular death, myocardial infarction, stroke, coronary revascularization or hospitalization for unstable angina. The trial will continue until 1600 patients reach the primary endpoint, with a median duration of therapy of 3 years. STRENGTH will determine whether Epanova 4 g daily will reduce cardiovascular events in statin‐treated high‐risk patients with hypertriglyceridemia and low HDL‐C levels.